Interface hydrophobic tunnel engineering: A general strategy to boost electrochemical conversion of N2 to NH3. (February 2022) - Du, Cheng; Qiu, Chenglong; Fang, Zhongying; Li, Ping; Gao, Yijing; Wang, Jianguo; Chen, Wei
Abstract: Electrocatalytic nitrogen reduction reaction (NRR), which can produce ammonia from N2 and H2 O under ambient conditions, has emerged as a promising sustainable alternative to the Haber-Bosch (H-B) process. However, their unsatisfied conversion efficiency and selectivity severely restrict the real utilization of NRR, owing to the stubborn triple bond in the N2 molecule and the competitive hydrogen evolution reaction (HER). Here, inspired from the local microenvironment of the nitrogenase, we report for the first time a facile and general strategy to boost the NRR selectivity and activity through the self-assembled monolayer (SAM) of hexanethiol (HEX) on a series of metal electrocatalysts (Cu, Au, Pt, Pd and Ni). Molecular dynamics (MD) simulations suggest that the HEX SAM provides a hydrophobic microenvironment to impede the diffusion and adsorption of water molecules and promote that of N2 molecules, thus inhibiting HER and simultaneously improving the NRR performance. Notably, among all the prepared samples, the highest Faradic efficiency (FE) of 50.5% is achieved on Cu-HEX with NH3 formation rate (R) of 1.2 μg h −1 cm −2 . Remarkably, for the HER-favored Pt catalyst, the highest R of 26.4 μg h −1 cm −2 is also achieved on Pt-HEX with FE of 1.8% under 1 cm 2 of electrode area. The present strategy not only represents a general diffusion-controlled method to engineer high-performance NRR electrocatalysts, but also provides a new insight into the effect of surface chemistry of catalysts on the NRR process and kinetics. Graphical Abstract: ga1 Highlights: Nitrogen reduction can be boosted by fabricating hexanethiol monolayer on metal surface. The hexanethiol monolayer can block water molecules to restrain the competitive HER. 50.5% Faradic efficiency is achieved on Cu-HEX with NH3 formation rate of 1.2 μg h −1 cm −2 . This work provides a general method to engineer high-performance NRR electrocatalysts.